Intensity of Stem Rot Disease in Dragon Fruit (Hylocereus polyrhizus) at Samboja Regency - nur adi (Jurnal Agroekoteknologi Tropika Lembab, 2018)
This study aims to determine the intensity of stem rot disease in dragon fruit plants in Samboja District Kutai Kartanegara Regency. This research was condu cted from November to December 2017 which is represented by four land i.e. two land located in Sungai Merdeka Village and two land located in Kelurahan Karya Merdeka. The method used in this research was interview and direct observation (survey). The sample was determined by purposive sampling or judgemental sampling method, that is method that chooses subject based on specified specific criteria (symptomatic plants) and sample of dragon fruits tems that attack disease in the field. The sample then isolated and identified the pathogen causing the disease at the Pest and Plant Disease Laboratory, Faculty of Agriculture Mulawarman University. The results of this study indicated that the percentage of stem rot disease in the District of Samboja KutaiKartanegara Regency of 60.83% with the severity of disease 36.12%. Results from the isolation of the ten drills of dragon fruit plants affected by stem rot disease identified the fungus Fusarium sp., Aspergillus sp. And Trichoderma sp.